2006
DOI: 10.1097/00042737-200606000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Functional bowel disorders in rotating shift nurses may be related to sleep disturbances

Abstract: FBD were more common and severe among rotating shift nurses. The FBD symptom score was positively and independently correlated with the sleep disturbance score, suggesting that poor sleep might be associated with increased FBD symptoms in rotating shift nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 16 publications
7
30
0
1
Order By: Relevance
“…Nojkov et al (2010) found similar results in nurses in the USA, in which the prevalence of IBS was 48% in rotating-shift nurses and 31% in day-shift nurses. A study from Singapore found the prevalence of functional bowel disorders to be 38% in nurses working rotating shifts and 20% in those working day shifts (Zhen et al, 2006). Using Rome III criteria and only nurses being included may explain this higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nojkov et al (2010) found similar results in nurses in the USA, in which the prevalence of IBS was 48% in rotating-shift nurses and 31% in day-shift nurses. A study from Singapore found the prevalence of functional bowel disorders to be 38% in nurses working rotating shifts and 20% in those working day shifts (Zhen et al, 2006). Using Rome III criteria and only nurses being included may explain this higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…One study in the USA found that nurses, especially those working on rotating shifts, were at a high risk for developing IBS (Nojkov et al, 2010). Zhen et al (2006) also demonstrated that IBS was common and severe among nurses working on rotating shifts, and sleep disturbance might be associated with IBS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…27 A group of female nurses on rotating shifts were observed to have significantly ( p < 0.0001) greater sleep disturbance based on subjective reports compared with day nurses. 28 The cited studies suggest that rotating shifts can impact sleep, but more gender-based research is needed to substantiate if this is the case and if certain shift schedules lead to greater sleep difficulties in female workers. Shift work sleep disorder is recognized by the American Academy of Sleep Medicine, but controversy exists as to (1) whether it is prudent to provide a medical treatment for sleep that is disturbed as a consequence of behavior, that is, shift work, rather than pathology, and (2) how long pharmacological treatments can safely be administered.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of IBS, psychological factors have been found to be of major importance, and poor sleep quality had been reported to adversely affect psychological factors in rotating shift workers [23] . However, sleep disturbances alone will not completely explain the association between shift work and IBS.…”
Section: Discussionmentioning
confidence: 99%